A novel design silicone oil removal cannula - Akkan, Fevzi; Dinc, Dincer (Asian Journal of Medical Sciences, 2021)
Background: Silicone oil, which is one of the most commonly used endotamponades in vitreoretinal surgery, is removed after a certain period of time in most cases. In this study, we present our results with a unique cannula that provides effective and safe silicone oil removal. Aims and Objectives: To assess the aids and success of silicone oil removal with a novel 23-gauge cannula for the patients who underwent pars plana vitrectomy and silicone oil injection before. Materials and Methods: 72 eyes of 64 patients who operated by the same surgeon (FA) between May 2017 and May 2019 were involved in the study. The primary indications were proliferative diabetic retinopathy in 46 (63.9%) eyes and retinal detachment in 26 (36.1%) eyes. Phacoemulsification and intraocular lens implantation (23 eyes), membrane peeling (23 eyes), internal limiting membrane peeling (5 eyes), and argon laser endo-photocoagulation (37 eyes) performed in the same session. Furthermore, perfluorocarbon remnants aspirated in 9 eyes and 17 eyes needed suturing. Descriptive statistical analyses achieved by SPSS 10.5 statistical software. Results: The mean follow-up time was 11.7 + 2.5 months (between 3 and 23 months), and the mean age was 61.4 + 8.52 years (between 44 and 69 years). 1000 centistokes (cSt) silicone oil was removed from 61 (84.7%) eyes, and 5000 cSt silicone oil was removed from 11 (15.3%) eyes. The mean removal time was 2.04 + 0.1 min for 1000 cSt silicone oil and 5.11 + 0.3 min for 5000 cSt silicone oil. 4 re-detachment and 3 vitreous hemorrhage observed in follow-up period. Post-operative silicone oil remnants were not detected in any patient. Conclusion: The unique 23-gauge cannula provides silicone oil removal without any conjunctival cut-down and sclerotomy enlargement. Thus, it reduces the duration of surgery and post-operative recovery period.